2022
DOI: 10.1002/clt2.12178
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for dysregulated glutamine metabolism in the asthmatic airway epithelium

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Recently, Bravo-Solarte et al, using bronchial brush samples, described genomic evidence of misregulated glutamine metabolism in airway epithelial cells from asthma patients [86]. Based on a secondary analysis of two openaccess microarray datasets from asthmatics and healthy controls, the authors found upregulation of enzymes involved in the glutamine metabolism including glutamic-oxaloacetic transaminase 1, glutamic-oxaloacetic transaminase 2, nitric oxide synthase 2, glutathione peroxidase 7, phosphoserine aminotransferase 1, pyrroline-5-carboxylate reductase 1, sirtuin 7, solute carrier family 7 member 11, and solute carrier family 39 member 8 [86].…”
Section: Asthmamentioning
confidence: 99%
“…Recently, Bravo-Solarte et al, using bronchial brush samples, described genomic evidence of misregulated glutamine metabolism in airway epithelial cells from asthma patients [86]. Based on a secondary analysis of two openaccess microarray datasets from asthmatics and healthy controls, the authors found upregulation of enzymes involved in the glutamine metabolism including glutamic-oxaloacetic transaminase 1, glutamic-oxaloacetic transaminase 2, nitric oxide synthase 2, glutathione peroxidase 7, phosphoserine aminotransferase 1, pyrroline-5-carboxylate reductase 1, sirtuin 7, solute carrier family 7 member 11, and solute carrier family 39 member 8 [86].…”
Section: Asthmamentioning
confidence: 99%